Home blood‐pressure monitoring in a hypertensive pregnant population: cost‐minimization study. (12th March 2019) - Xydopoulos, G.; Perry, H.; Sheehan, E.; Thilaganathan, B.; Fordham, R.; Khalil, A.
ABSTRACT: Objective: Traditional blood‐pressure monitoring in hypertensive pregnant women requires frequent visits to the maternity outpatient services. Home blood‐pressure monitoring (HBPM) could offer a cost‐saving alternative that is acceptable to patients. The aim of this study was to undertake a health economic analysis of HBPM compared with traditional monitoring in hypertensive pregnant women. Methods: This was a cost‐minimization study of hypertensive pregnant women who had HBPM with or without the adjunct of a smartphone application (App), via a specially designed pathway, and a control group managed according to the local protocol of regular hospital visits for blood‐pressure monitoring. Outcome measures were the number of outpatient visits, inpatient bed stays and investigations performed. Maternal, fetal and neonatal adverse outcomes were also recorded. Health economic analysis was performed using direct cost comparison of the study dataset and process scenario modeling. Results: The HBPM group included 108 women, of whom 29 recorded their results on the smartphone App and 79 in their notes. The control group comprised 58 patients. There were significantly more women with chronic hypertension in the HBPM group than in the control group (49.1% vs 25.9%, P  = 0.004). The HBPM group had significantly longer duration of monitoring (9 weeks vs 5 weeks, P  = 0.004) and started monitoring at an earlier gestational age (30.0 weeks vs 33.6 weeks, P  = 0.001) compared with the control group. Despite these differences, the mean saving per week for each patient using HBPM compared with traditional monitoring was £200.69, while for each HBPM patient using the smartphone App, the weekly saving was £286.53 compared with the control group. The process modeling method predicted weekly savings of between £98.32 and £245.80 per patient using HBPM compared with traditional monitoring. Conclusion: HBPM in hypertensive pregnancy appears to be cost saving compared with traditional monitoring, without compromising maternal, fetal or neonatal safety. Larger studies are required to confirm these findings. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.